An eco-compatible strategy for the diversity-oriented synthesis of macrocycles exploiting carbohydrate-derived building blocks - Maurya, Sushil K.; Rana, Rohit (Beilstein Journal of Organic Chemistry, 2017)
An efficient, eco-compatible diversity-oriented synthesis (DOS) approach for the generation of library of sugar embedded macrocyclic compounds with various ring size containing 1,2,3-triazole has been developed. This concise strategy involves the iterative use of readily available sugar-derived alkyne/azide–alkene building blocks coupled through copper catalyzed azide–alkyne cycloaddition (CuAAC) reaction followed by pairing of the linear cyclo-adduct using greener reaction conditions. The eco-compatibility, mild reaction conditions, greener solvents, easy purification and avoidance of hazards and toxic solvents are advantages of this protocol to access this important structural class. The diversity of the macrocycles synthesized (in total we have synthesized 13 macrocycles) using a set of standard reaction protocols demonstrate the potential of the new eco-compatible approach for the macrocyclic library generation.
Keywords: carbohydrate; click chemistry; diversity-oriented synthesis; macrocycles; ring-closing metathesis

(untitled) - Brandt, W.; Haupt, J. V.; Wessjohann, L. A. (Curr. Top. Med. Chem., 2010)

(untitled) - Mallinson, J.; Collins, I. (Future Med. Chem., 2012)

(untitled) - Driggers, E. M.; Hale, S. P.; Lee, J.; Terrett, N. K. (Nat. Rev. Drug Discovery, 2008)

(untitled) - Collins, S.; Bartlett, S.; Nie, F.; Sore, H. F.; Spring, D. R. (Synthesis, 2016)

(untitled) - Jarikote, D. V.; Murphy, P. V. (Eur. J. Org. Chem., 2010)

(untitled) - Xie, J.; Bogliotti, N. (Chem. Rev., 2014)

(untitled) - Madsen, C. M.; Clausen, M. H. (Eur. J. Org. Chem., 2011)

(untitled) - Dörner, S.; Westermann, B. (Chem. Commun., 2005)

(untitled) - Adhikary, N. D.; Chattopadhyay, P. (J. Org. Chem., 2012)

(untitled) - Rao, N. S. J.; Raghunathan, R. (Tetrahedron Lett., 2015)

(untitled) - Fürstner, A. (Eur. J. Org. Chem., 2004)

(untitled) - Pereda-Miranda, R.; Bah, M. (Curr. Top. Med. Chem., 2003)

(untitled) - Raghunathan, D.; Sánchez-pedregal, V. M.; Junker, J.; Schwiegk, C.; Kalesse, M.; Kirschning, A.; Carlomagno, T. (Nucleic Acids Res., 2006)

(untitled) - Fürstner, A.; Albert, M.; Mlynarski, J.; Matheu, M.; DeClecq, E. (J. Am. Chem. Soc., 2003)

(untitled) - Nicolaou, K. C.; Snyder, S. A.; Montagnon, T.; Vassilikogiannakis, G. (Angew. Chem., Int. Ed., 2002)

(untitled) - Casiraghi, G.; Zanardi, F.; Appendino, G.; Rassu, G. (Chem. Rev., 2000)

(untitled) - Xu, L.; Li, Y.; Li, Y. (Asian J. Org. Chem., 2014)

(untitled) - Isidro-Llobet, A.; Georgiou, K. H.; Galloway, W. R. J. D.; Giacomini, E.; Hansen, M. R.; Méndez-Abt, G.; Tan, Y. S.; Carro, L.; Sore, H. F.; Spring, D. R. (Org. Biomol. Chem., 2015)

(untitled) - Wells, J. A.; McClendon, C. L. (Nature, 2007)

(untitled) - Beckmann, H. S. G.; Nie, F.; Hagerman, C. E.; Johansson, H.; Tan, Y. S.; Wilcke, D.; Spring, D. R. (Nat. Chem., 2013)

(untitled) - Hansen, E. C.; Lee, D. (J. Am. Chem. Soc., 2004)

(untitled) - Ghosh, A. K.; Bilcer, G.; Harwood, C.; Kawahama, R.; Shin, D.; Hussain, K. A.; Hong, L.; Loy, J. A.; Nguyen, C.; Koelsch, G.; Ermolieff, J.; Tang, J. (J. Med. Chem., 2001)

(untitled) - Trnka, T. M.; Grubbs, R. H. (Acc. Chem. Res., 2001)

(untitled) - Leeuwenburgh, M. A.; Van der Marel, G. A.; Overkleeft, H. S. (Curr. Opin. Chem. Biol., 2003)

(untitled) - Schrock, R. R.; Hoveyda, A. H. (Angew. Chem., Int. Ed., 2003)

(untitled) - Grubbs, R. H. (Tetrahedron, 2004)

(untitled) - Deiters, A.; Martin, S. F. (Chem. Rev., 2004)

(untitled) - Hong, S. H.; Sanders, D. P.; Lee, C. W.; Grubbs, R. H. (J. Am. Chem. Soc., 2005)

(untitled) - Chen, G.-w.; Kirschning, A. (Chem. – Eur. J., 2002)

(untitled) - Monfette, S.; Fogg, D. E. (Chem. Rev., 2009)

(untitled) - Pérez de Vega, M. J.; García-Aranda, M. I.; Gonáalez-Muñiz, R. (Med. Res. Rev., 2011)

(untitled) - Isidro-Llobet, A.; Murillo, T.; Bello, P.; Cilibrizzi, A.; Hodgkinson, J. T.; Galloway, W. R. J. D.; Bender, A.; Welch, M.; Spring, D. R. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Marsault, E.; Peterson, M. L. (J. Med. Chem., 2011)

(untitled) - Alvarez, R.; Velazquez, S.; San-Felix, A.; Aquaro, S.; De Clercq, E.; Perno, C.-F.; Karlsson, A.; Balzarini, J.; Camarasa, M. J. (J. Med. Chem., 1994)

(untitled) - Genin, M. J.; Alwine, D. A.; Anderson, D. J.; Barbachyn, M. R.; Emmert, D. E.; Garmon, S. A.; Graber, D. R.; Grega, K. C.; Hester, J. B.; Hutchinson, D. K.; Morris, J.; Reischer, R. J.; et al. (J. Med. Chem., 2000)

(untitled) - Laurent, B. A.; Grayson, S. M. (J. Am. Chem. Soc., 2006)

(untitled) - Tiwari, V. K.; Mishra, B. B.; Mishra, K. B.; Mishra, N.; Singh, A. S.; Chen, X. (Chem. Rev., 2016)

(untitled) - Chandrasekhar, S.; Rao, C. L.; Nagesh, C.; Reddy, C. R.; Sridhar, B. (Tetrahedron Lett., 2007)

(untitled) - Jogula, S.; Dasari, B.; Khatravath, M.; Chandrasekar, G.; Kitambi, S. S.; Arya, P. (Eur. J. Org. Chem., 2013)

Click Chemistry in Glycoscience - Potopnyk, M. A.; Jarosz, S. (“Sweet” Sucrose Macrocycles via a “Click Chemistry” Route, 2013)

(untitled) - Kolb, H. C.; Sharpless, K. B. (Drug Discovery Today, 2003)

(untitled) - Whiting, M.; Tripp, J. C.; Lin, Y.-C.; Lindstrom, W.; Olson, A. J.; Elder, J. H.; Sharpless, K. B.; Fokin, V. V. (J. Med. Chem., 2006)

Drug Design Research Perspectives - Wilkinson, B. L.; Bornaghi, L. F.; Houston, T. A.; Poulsen, S.-A. (Nova: Hauppauge, 2007)

(untitled) - Wang, Q.; Chan, T. R.; Hilgraf, R.; Fokin, V. V.; Sharpless, K. B.; Finn, M. G. (J. Am. Chem. Soc., 2003)

(untitled) - Hawker, C. J.; Fokin, V. V.; Finn, M. G.; Sharpless, K. B. (Aust. J. Chem., 2007)

(untitled) - Mulla, K.; Shaik, H.; Thompson, D. W.; Zhao, Y. (Org. Lett., 2013)

(untitled) - Hui, P.; Chandrasekar, R. (Adv. Mater., 2013)

(untitled) - Busseron, E.; Coutrot, F. (J. Org. Chem., 2013)

(untitled) - Campo, V. L.; Ivanova, I. M.; Carvalho, I.; Lopes, C. D.; Carneiro, Z. A.; Saalbach, G.; Schenkman, S.; da Silva, J. S.; Nepogodiev, S. A.; Field, R. A. (Tetrahedron, 2015)

(untitled) - Grimwood, M. E.; Hansen, H. C. (Tetrahedron, 2009)

(untitled) - Ghorai, A.; Padmanaban, E.; Mukhopadhyay, C.; Achari, B.; Chattopadhyay, P. (Chem. Commun., 2012)

(untitled) - Dörner, S.; Westermann, B. (Chem. Commun., 2005)

(untitled) - Elchert, B.; Li, J.; Wang, J.; Hui, Y.; Rai, R.; Ptak, R.; Ward, P.; Takemoto, J. Y.; Bensaci, M.; Chang, C.-W. T. (J. Org. Chem., 2004)

(untitled) - Ciardiello, J. J.; Galloway, W. R. J. D.; O’Connor, C. J.; Sore, H. F.; Stokes, J. E.; Wu, Y.; Spring, D. R. (Tetrahedron, 2016)

(untitled) - Nie, F.; Kunciw, D. L.; Wilcke, D.; Stokes, J. E.; Galloway, W. R. J. D.; Bartlett, S.; Sore, H. F.; Spring, D. R. (Angew. Chem., Int. Ed., 2016)

(untitled) - Rapi, Z.; Ozohanics, O.; Tóth, G.; Bakó, P.; Höfler, L.; Nemcsok, T.; Kánya, N.; Keglevich, G. (J. Inclusion Phenom. Macrocyclic Chem., 2016)

(untitled) - Skowerski, K.; Białecki, J.; Tracz, A.; Olszewski, T. K. (Green Chem., 2014)
and references cited therein

(untitled) - Alder, C. M.; Hayler, J. D.; Henderson, R. K.; Redman, A. M.; Shukla, L.; Shuster, L. E.; Sneddon, H. F. (Green Chem., 2016)

(untitled) - Nielsen, T. E.; Schreiber, S. L. (Angew. Chem., Int. Ed., 2008)

(untitled) - Morton, D.; Leach, S.; Cordier, C.; Warriner, S.; Nelson, A. (Angew. Chem., Int. Ed., 2009)

(untitled) - Marcaurelle, L. A.; Comer, E.; Dandapani, S.; Duvall, J. R.; Gerard, B.; Kesavan, S.; Lee IV, M. D.; Liu, H.; Lowe, J. T.; Marie, J.-C.; Mulrooney, C. A.; Pandya, B. A.; et al. (J. Am. Chem. Soc., 2010)

(untitled) - Hajduk, P. J.; Galloway, W. R. J. D.; Spring, D. R. (Nature, 2011)

(untitled) - Maurya, S. K.; Dow, M.; Warriner, S.; Nelson, A. (Beilstein J. Org. Chem., 2013)

(untitled) - Van Maarseveen, J. H.; Horne, W. S.; Ghadiri, M. R. (Org. Lett., 2005)

(untitled) - Oh, K.; Guan, Z. (Chem. Commun., 2006)

(untitled) - Whiting, M.; Muldoon, J.; Lin, Y.-C.; Silverman, S. M.; Lindstrom, W.; Olson, A. J.; Kolb, H. C.; Finn, M. G.; Sharpless, K. B.; Elder, J. H.; Fokin, V. V. (Angew. Chem., Int. Ed., 2006)